Much More Than Just Money: Investigating Remittances Across Time and Place in the Eritrean Context - Milena Belloni; Valentina Fusari; Aurora Massa (Modern Africa, 2022)
Remittances have played crucial and shifting roles in Eritrea and its diaspora. They were fundamental to the achievement of national independence and are a resource with which the current government strengthens its power. Households have been reliant on remittances for survival, while for migrants they have been crucial to reinforce their sense of national belonging. Drawing from fieldwork, this article analyses remittances as a powerful tool to assess the ongoing (dis)connection between segments of the Eritrean diaspora and their homeland. The article firstly addresses financial remittances and shows how (in)formal flows play differing functions in relation to the government, communities, and families. Aft er highlighting how social remittances are contributing to current transformations within Eritrean society, it reflects on the potential role remittances may play in the future of the country.